2022
DOI: 10.3389/pore.2022.1610481
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Co-Expression Modules and Genes Associated With Tumor Progression in Oral Squamous Cell Carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is a common head-and-neck cancer with a deficiency of early diagnosis and poor prognosis. To identify potential diagnostic and prognostic markers of OSCC, we firstly used weighted gene co-expression network analysis (WGCNA) to build a co-expression module from GSE42743. Next, we performed Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses on specified units from selected modules utilizing Database for Annotation, Visualization, and Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Subsequently, Sun et al [ 56 ] used the GEPIA web server to validate their experimental results; this included evaluating the mRNA expression levels of AKT1 and PLK1 in HNSCC than in healthy tissues and analyzing the prognostic effect of the genes in patients with HNSCC. Fang et al [ 57 ] identified several genes with a correlation score >0.8 in a PPI network associated with the pathogenesis of OSCC. Next, the authors used the GEPIA tool to evaluate the prognostic role of the genes in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Sun et al [ 56 ] used the GEPIA web server to validate their experimental results; this included evaluating the mRNA expression levels of AKT1 and PLK1 in HNSCC than in healthy tissues and analyzing the prognostic effect of the genes in patients with HNSCC. Fang et al [ 57 ] identified several genes with a correlation score >0.8 in a PPI network associated with the pathogenesis of OSCC. Next, the authors used the GEPIA tool to evaluate the prognostic role of the genes in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of VRK1, detected using microarray transcriptomic platforms, is associated with poor prognosis of cancer such as breast 141 , lung 142,143 , head and neck squamous cell carcinomas 127 , colon 144 , liver 145 , gliomas 146,147 , multiple myeloma 148 , esophageal carcinomas 149 , and oral cancer 150 . For example, VRK1 expression positively correlates with glioma pathological grade and its depletion in glioblastoma cells alters DDR and promotes tumor cells death 146,151 .…”
Section: Vrk1 Implications In Cancermentioning
confidence: 99%
“…Briefly, the role of VRK1 in cancer epigenetics is still unclear and requires further research, but it is known that VRK1 overexpression is related to poor prognosis in many tumor types such as breast, lung, head and neck squamous cell carcinomas, colon, liver, gliomas, multiple myeloma, esophageal carcinomas, and oral cancer 127,[141][142][143][144][145][146][147][148][149][150] . This makes VRK1 a good candidate to target from an epigenetic therapeutic approach.…”
Section: Vrk1 Absence But Not Vrk1 Inhibition Provokes Widespread Chr...mentioning
confidence: 99%